Application of RCM Principles in the Air Operations - Beno, Ludek; Bugaj, Martin; Novak, Andrej (Communications - Scientific letters of the University of Zilina, 2005)
Maintenance organizations assist in ensuring that all aircraft, their systems and parts are operated or maintained under controlled conformity to national and international airworthiness standards. Ensuring that these standards are met involves a vast network of organizations and personnel. To develop and then to comply with effective standards and procedures for maintenance program is never-ending process, which is responsible for the coordination and management of all maintenance activities and consequently manufacturing activities too. The RCM program provides a logical way of determining if preventive maintenance makes sense for a given part, system or the whole aircraft. The RCM concept completely changes the way in which the preventive maintenance is viewed. It is widely accepted fact that not all parts benefit from preventive maintenance.